2015
DOI: 10.1208/s12248-015-9736-6
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Orally Inhaled Drug Products

Abstract: Abstract. The presentations at the Orlando Inhalation Conference on pharmacokinetic (PK) studies indicated that PK is the most sensitive methodology for detecting formulation differences of oral inhaled drug products (OIDPs) that have negligible gastrointestinal bioavailability or for which oral absorption can be prevented (e.g., ingestion of charcoal). PK studies, therefore, may represent the most appropriate methodology for assessing local and systemic bioequivalence (BE). It was believed by many (but not al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 8 publications
0
27
0
Order By: Relevance
“…The EMA currently suggests a stepwise evaluation of in vitro and in vivo pharmacokinetic and pharmacodynamics studies, while the US-FDA endorses an 'aggregate weight of evidence' approach for establishing the bioequivalence of inhalation drugs (Apiou-Sbirlea et al, 2013;Lu et al, 2015). Even though the performance of a bioequivalence study is not always considered sufficient to establish therapeutic equivalence between two locally acting orally inhaled drugs (Lu et al, 2015), and certain critical issues when conducting such studies exist (Thakkar, Mhatre, Jadhav, Goswami, & Shah, 2015), PK studies are still considered the most sensitive methodology in detecting differences between two inhalation drug products (Hochhaus, Horhota, Hendeles, Suarez, & Rebello, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The EMA currently suggests a stepwise evaluation of in vitro and in vivo pharmacokinetic and pharmacodynamics studies, while the US-FDA endorses an 'aggregate weight of evidence' approach for establishing the bioequivalence of inhalation drugs (Apiou-Sbirlea et al, 2013;Lu et al, 2015). Even though the performance of a bioequivalence study is not always considered sufficient to establish therapeutic equivalence between two locally acting orally inhaled drugs (Lu et al, 2015), and certain critical issues when conducting such studies exist (Thakkar, Mhatre, Jadhav, Goswami, & Shah, 2015), PK studies are still considered the most sensitive methodology in detecting differences between two inhalation drug products (Hochhaus, Horhota, Hendeles, Suarez, & Rebello, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of inhaled COPD treatments is associated with the presence of the drug in the lungs [12]; however, absorption into the systemic circulation may elicit additional pharmacologic effects that could influence the safety and tolerability profile of the drug. [13] Previous studies have found that the pharmacokinetic (PK) profiles of BGF MDI and GFF MDI were comparable between Western and Japanese healthy adults.…”
Section: Introductionmentioning
confidence: 97%
“…However, when plotted in Figure , these k a values of FP were found to be far lower than the value predicted from MW and K D ‐dependent diffusion. This suggested that the lung absorption of fluticasone propionate was unusually slow (a half‐life of ~3.5 h) and thus rate‐limited by a mechanism other than lung membrane diffusion, such as dissolution due to poor aqueous solubility (~0.1 μg/ml), as has been attributed elsewhere (Hochhaus, Horhota, Hendeles, Suarez, & Rebello, ; Sakagami & Arora‐Lakhani, ). In contrast, the k nad values were different in the MDI and DPI delivery, and the DPI delivery resulted in a greater k nad value (faster non‐absorptive disposition) than the MDI delivery (Table ).…”
Section: Resultsmentioning
confidence: 70%
“…In contrast, the k nad values were different in the MDI and DPI delivery, and the DPI delivery resulted in a greater k nad value (faster non‐absorptive disposition) than the MDI delivery (Table ). Like CPFX, the non‐absorptive disposition of FP in the lung was primarily due to mucociliary clearance (Hochhaus et al, ; Sakagami & Arora‐Lakhani, ). If so, this greater k nad value for the DPI would make sense, given that its 12% of the in vitro DTL in a size < 2 μm, compared with 33% for MDI (Table ), predicted a shallower lung regional deposition and faster mucociliary clearance.…”
Section: Resultsmentioning
confidence: 99%